(3TQM MeGSI CHj JeGes - (3CHh YHO Gddg MSjf Hf Ydj Hf YHO Gddg GdfeQis; (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s ((3CMeO Hf HcQ Hf CMeO ,GdMGce KZQ Nhi s)
(3ChdgG (B:s
(3bGd YHO Gddg gPG TQM eYGfi cJGH GdMeGSg , hPcQ GdJi gi ai GdNW Ydi UhQI hGMOI Ydi GFJdGa GdeYGfi hGNJdGagG s
(3BNQgG (B:s
(3CNPJ GdOjI aTQHJ ef CdHGfgG acCfi bO TQHJ OekG (B: (3hbhdg (B: (3HYjOg eghi GdbQW , Ci Whjdg GdYfb Je GdcJGH HCSQg s
(3fSNI ebQhAI heUMMI heYGQVI s
(3hHBNQgG fU ebGHdIs
(3hChQGbgG eVWQHI GdJQJjHs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQI GdYfhGf (B:s
Keywords: (3GdCOHs